The REACH 2010 Logic Model: An Illustration of Expected Performance - Leandris Liburd, MPH, MA; Wayne H. Giles, MD, MS; Youlian Liao, MD; Pattie Tucker, DrPH, MPH (Centers for Disease Control and Prevention, 2006)
The Centers for Disease Control and Prevention (CDC) supports 40 Racial and Ethnic Approaches to Community Health (REACH 2010) community coalitions in designing, implementing, and evaluating community-driven strategies to eliminate health disparities in racial and ethnic groups. The REACH 2010 logic model was developed to assist grantees in identifying, documenting, and evaluating local attributes of the coalition and its partners to reduce and eliminate local health disparities. The model emphasizes the program's theory of change for addressing health disparities; it displays five distinct stages of evaluation for which qualitative and quantitative measurement data are collected. The CDC is relying on REACH 2010 grantees to provide credible evidence that explains how community contributions have changed conditions and behaviors, thus leading to the reduction and elimination of health disparities.